Devolution in Sri Lanka : S.W.R.D. Bandaranaike and the debate on power sharing - Bandaranaike, S. W. R. D. (Solomon West Ridgeway Dias); De Silva, K. M.; International Centre for Ethnic Studies (Kandy : International Centre for Ethnic Studies, 1996)
Decentralizaton and devolution of power in Sri Lanka; consists of documents relating to attempts to introduce legislation on provincial councils by a former prime minister.
Keywords: Decentralization in government -- Sri Lanka; Constitutional amendments -- Sri Lanka; Sri Lanka -- Ethnic relations